Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1523-1755.2003.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease, anemia, and incident stroke in a middle-aged, community-based population: The ARIC Study

Abstract: Among middle-aged, community-based persons, the combination of CKD and anemia was associated with a substantial increase in stroke risk, independent of other known risk factors for stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
196
2
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(217 citation statements)
references
References 24 publications
11
196
2
8
Order By: Relevance
“…Anemia is highly prevalent among people with reduced kidney function attributed to decreased synthesis of erythropoietin,7 iron deficiency,8 and chronic inflammation,9 and it contributes to increased cardiac workload10 and left ventricular hypertrophy 11. Previous studies showed that the association of reduced kidney function was stronger in anemia with the risk of coronary heart disease12 and stroke 13…”
mentioning
confidence: 99%
“…Anemia is highly prevalent among people with reduced kidney function attributed to decreased synthesis of erythropoietin,7 iron deficiency,8 and chronic inflammation,9 and it contributes to increased cardiac workload10 and left ventricular hypertrophy 11. Previous studies showed that the association of reduced kidney function was stronger in anemia with the risk of coronary heart disease12 and stroke 13…”
mentioning
confidence: 99%
“…7 Published data suggest that anemia is an independent risk factor for cardiovascular morbidity and mortality, 8 and the combination of anemia and CKD is associ-ated with a significantly higher stroke risk. 9 CVD is the foremost cause of mortality in the CKD population, accounting for nearly half of the overall mortality. 10 Even mild renal insufficiency is linked to a higher risk of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…n patients who have chronic kidney disease (CKD) and are not yet on hemodialysis (HD), anemia has a significant prevalence, rising from approximately 15 to 70% in stages 3 to 5 (1-4), and acts as an independent risk factor for cardiovascular disease (2,(5)(6)(7)(8) and ESRD (8 -10). These findings have led to the recommendations, recently reiterated by European (European Best Practice Guidelines) and US (Kidney Disease Outcomes Quality Initiative) clinical practice guidelines (11,12), to prescribe erythropoiesis-stimulating agents (ESA) to maintain hemoglobin Ն11 g/dl in all patients with CKD.…”
mentioning
confidence: 99%